Amazon develops Scottish centre. (Bookseller, 2004)
This article reports that the Scottish Executive is to contribute up to £250,000 towards the company Amazon's new software development centre in Edinburgh, Scotland. The centre will work on new features for Amazon's six web sites. It is expected to open in the second half of 2004. It will employ 40 computer scientists and software engineers by 2006. Amazon said Edinburgh was chosen for an abundance of computer sciences staff. The development of Amazon's Great Britain-based operations follows strong international sales growth.